Perlindungan Hukum terhadap Nasabah Bank atas Tindak Pidana Pencatatan Palsu dalam Dokumen Perbankan - I Kadek Duta Anugrah; I Made Minggu Widyantara; Desak Gde Dwi Arini (Jurnal Preferensi Hukum, 2022)
This study aims to analyze and describe banking crimes, as well as how legal protection given to customers who are concerned about the existence of a criminal act of false recording in banking documents. With the increasing number of activities that banks carry out, with that many individuals or groups have intentions that are contrary to applicable law, whether it be with anything, such as false records. The problems discussed are how to overcome banking crimes, as well as how legal protection given to customers regarding the existence of fraudulent recording crimes in banking documents. This research is a type of normative legal research to explore it. From the results of the study, it was shown that the handling of banking crimes had been going well, it was shown by Bank Indonesia having implemented preventive measures, namely by increasing working relations with relevant agencies, as well as repressive efforts, namely by conducting investigations on the basis of related laws. Regarding legal protection that must be carried out by banks, it is divided into indirect protection in the form of the bank using the principle of prudence in the implementation of banking activities, as well as direct protection in the form of a deposit insurance institution where this institution will guarantee customer deposits of a maximum of two billion rupiah if this occurs. things that are detrimental to customers.